Recurrence of fatty liver disease following liver transplantation for NAFLD-related cirrhosis: Current status and challenges - Arash Dooghaie Moghadam; Pegah Eslami; Niloofar Razavi-Khorasani; Bobak Moazzami; Kamyab Makhdoomi Sharabiani; Ermia Farokhi; Alireza Mansour-Ghanaei; Farbod Zahedi-Tajrishi; Azim Mehrvar; Morteza Aghajanpoor Pasha; Sandra Saeedi; Shahrokh Iravani (Babol University of Medical Sciences, 2020)
Non-alcoholic fatty liver disease (NAFLD) is emerging as a major health problem worldwide. NAFLD is a continuum of disease ranging from mild liver steatosis to severe steatohepatitis, which will ultimately lead to end-stage liver disease with high morbidity and mortality rates. This disorder is considered as a silent liver disease. The metabolic syndrome and its components are accounted as the major risk factors for the progression of NAFLD to NASH and cirrhosis. Liver transplantation is considered as an appropriate treatment for the end-stage disease. For the last two decades, NASH has been the most common reason for liver transplantation, especially in the developed countries; however, the outcome of post-transplantation in these patients is of a great concern. The recurrent NASH and NAFLD seem to be the usual issues in LT. Steatosis appears in more than 80% of LTs; however, re-transplantation caused by steatohepatitis is rare. Recently, several risk factors of the recurrent NAFLD, including age, donor steatosis, metabolic syndrome, and immunosuppressant agents, have been introduced. Among the metabolic syndrome components, obesity seriously has negative effects on the outcomes of post-liver transplantation in patients. Unfortunately, there is no standard medicine to prevent or treat the recurrent NAFLD; however, it seems that weight loss and lifestyle modification play critical roles in controlling or inhibiting the recurrent NAFLD or NASH.